The Implementation of Everyone Is A Teacher Strategy To Improve Learning Outcomes In Tajweed Subject at Class 1 Int PMDG Putri 2 - Lutfina Aribah; Ainun Amalia; Saiful Anwar (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
This study examines the effect of the “Everyone Is A Teacher” learning method on learning outcomes of Tajweed subjects in grade 1 students at Pondok Modern Gontor Putri 2. Using a quasi-experimental design and quantitative approach, 40 students were divided into experimental and control groups. Data was collected through tests measuring Tajweed comprehension as well as observations of students' active participation and engagement. The results of the analysis showed that the strategy significantly improved student learning outcomes, with a mean difference of 1,800 points and a p-value of 0.001, supporting the effectiveness of the method. In addition to improving understanding of the material, the strategy also encourages active participation, collaboration, as well as the development of soft skills such as self- confidence and leadership. The findings confirm that innovation in participatory and interactive learning methods can overcome the challenges of traditional learning, particularly in religious education and create a more engaging and meaningful learning atmosphere. The results recommend the application of this method to improve the quality of learning in religious and general education institutions.